Sosialisasi Pengenalan Uji Sondir untuk Evaluasi Daya Dukung Tanah Bangunan Masjid Jami’ Raudhatul Jannah, Wilayah Jakarta Timur - Era Agita Kabdiyono; Alizar Alizar; Muslim Untung; Nabiyanka Ardhiansyah; Wulan Muchidayat (Asosiasi Dosen Muda Indonesia, 2026)
This community service activity aimed to introduce and implement Cone Penetration Testing (CPT) or sondir testing as an initial method for evaluating soil bearing capacity in the construction plan of Masjid Jami’ Raudhatul Jannah, located in East Jakarta. Soil investigation plays a crucial role in ensuring the structural safety and stability of buildings, particularly for public facilities such as mosques. The program was conducted through field observations, technical explanations, and direct demonstrations of CPT procedures to mosque administrators and local community representatives. The test results provided information regarding soil stratification, cone resistance, and estimated bearing capacity at the proposed construction site. The activity also enhanced participants’ understanding of the importance of geotechnical investigations prior to construction work. Through this program, the community gained practical knowledge about soil testing methods and their contribution to minimizing structural risks and supporting sustainable building development. The implementation of CPT testing is expected to become a reference for future construction planning in the area.